A Single-Center Analysis of Sex Differences in Patients With Chronic Subdural Hematoma in China - Ou, Yunwei; Fan, Wenhua; Yu, Xiaofan; Wu, Liang; Liu, Weiming (Frontiers in Neurology, 2022)
Background: Given the male predominance in the prevalence of chronic subdural hematoma (CSDH), we investigated the relationship between sex differences and clinical features of CSDH. Methods: We retrieved a large collection of clinical factors from CSDH patients between August 2011 and May 2019, and we analyzed the diﬀerences and similarities in the clinical data and outcomes between men and women. Results: 1,307 CSDH patients were enrolled in the present study. When we did not account for age, a greater proportion of women relative to men manifested diabetes (p=0.001) and cardiac disease (p=0.035) prior to the onset of CSDH. Regarding recovery outcome and recurrence rate, we observed no significant differences between men and women. The sole difference between female and male patients after surgery was that women experienced more complications than men (p=0.044), and both length of hospital stay (p<0.001, B=0.159, Exp[B]=1.172, 95% CI=1.078–1.274) and presence of cardiac disease (p=0.002, B=2.063, Exp[B]=7.867, 95% CI=2.167–28.550) were identiﬁed as independent risk factors. After accounting for age, women with CSDH exhibited more frequent disorders of consciousness at admission than did males in group of ≤40-year-old patients (p=0.018), while proportion of women with diabetes was higher than that of men in 41–79-year-old group (p<0.001). However, female patients after surgery experienced more complications(p=0.047), longer length of hospital stay (p=0.005), and higher mortality at discharge(p=0.035) than did male patients in middle-aged group. Finally, length of hospital stay(p<0.001, B=0.186, Exp[B]=1.205, 95% CI=1.091–1.331) and cardiac disease(p=0.017, B=2.040, Exp[B]=7.693, 95% CI=1.430–41.372) impacted occurrence of complications in women 41–79-year-old, while duration of drainage catheter use (p<0.001, B=1.132, beta=0.280) and complications(p<0.001, B=5.615, beta=0.366) were identiﬁed as independent risk factors for length of hospital stay in the same group of women. Conclusions: Although sex differences did not constitute a crucial factor in all of the CSDH patients, we still need to pay closer attention to disparities between men and women with respect to complications, length of hospital stay, and mortality at discharge in the various age groups (particularly with respect to 41–79-year-old female patients), in order to provide satisfactory management and treatment of CSDH patients.